Pharmacogenomic‐based personalized medicine: Multistakeholder perspectives on implementational drivers and barriers in the Canadian healthcare system - Mathushan Subasri (Wiley, 2021)
Abstract Pharmacogenomics (PGx)‐based personalized medicine (PM) is increasingly utilized to guide treatment decisions for many drug‐disease combinations. Notably, London Health Sciences Centre (LHSC) has pioneered a PGx program that has become a staple for London‐based specialists. Although implementational studies have been conducted in other jurisdictions, the Canadian healthcare system is understudied. Herein, the multistakeholder perspectives on implementational drivers and barriers are elucidated. Using a mixed‐method qualitative model, key stakeholders, and patients from LHSC’s PGx‐based PM clinic were interviewed and surveyed, respectively. Interview transcripts were thematically analyzed in a stepwise process of customer profiling, value mapping, and business model canvasing. Value for LHSC located specialist users of PGx was driven by the quick turnaround time, independence of the PGx clinic, and the quality of information. Engagement of external specialists was only limited by access and awareness, whereas other healthcare nonusers were limited by education and applicability. The major determinant of successful adoption at novel sites were institutional champions. Patients valued and approved of the service, expressed a general willingness to pay, but often traveled far to receive genotyping. This paper discusses the critical pillars of education, awareness, advocacy, and efficiency required to address implementation barriers to healthcare service innovation in Canada. Further adoption of PGx practices into Canadian hospitals is an important factor for advancing system‐level changes in care delivery, patient experiences, and outcomes. The findings in this paper can help inform efforts to advance clinical PGx practices, but also the potential adoption and implementation of other innovative healthcare service solutions.